2017
DOI: 10.1016/j.bjorl.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

The sphenoid sinus, foramen rotundum and vidian canal: a radiological study of anatomical relationships

Abstract: The results of this study can be used to provide a better anatomical understanding of the area, which is necessary for endoscopic skull base surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 10 publications
1
26
0
1
Order By: Relevance
“…Liu et al (22) reported in their study that type 1 was 53.4%, type 2 was 34.2%, and type 3 was 12.5%. Mohebbi et al (17) reported in the radiological study they performed that type 1 was 28%, type 2 was 48%, and type 3 was 24%. In this study, while type 1 was 33.8%, type 2 was 29.7%, and type 3 was 36.5% on the right side, type 1 was 36.4%, type 2 was 27.4%, and type 3 was 36.2% on the left side.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Liu et al (22) reported in their study that type 1 was 53.4%, type 2 was 34.2%, and type 3 was 12.5%. Mohebbi et al (17) reported in the radiological study they performed that type 1 was 28%, type 2 was 48%, and type 3 was 24%. In this study, while type 1 was 33.8%, type 2 was 29.7%, and type 3 was 36.5% on the right side, type 1 was 36.4%, type 2 was 27.4%, and type 3 was 36.2% on the left side.…”
Section: Discussionmentioning
confidence: 98%
“…Naturally, the Vidian canal is located in the inferolateral of the internal carotid artery. The internal carotid artery is bordered by the Vidian canal in the inferolateral and by the mandibular nerve in the superolateral portion (17). The Vidian canal is formed as a result of the pterygoid process and the emergence of the large wing of the sphenoid bone (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anterior clinoid pneumatisation was frequently associated with type 2 (31%), type 3(54%). Lateral recess or pterygoid recess pneumatisation (16) is defined as pneumatisation extending beyond the imaginary line joining the foramen rotundum and Vidian's nerve. This sets the neurovascular structures prone for injury during endonasal approach.…”
Section: Discussionmentioning
confidence: 99%
“…en vertical de 6,22 mm(117). El agujero redondo se encuentra separado de la línea media por 19 mm(154). La longitud del canal palatovaginal es de 7,15 mm, formando un ángulo de 48º con el canal vidiano y la distancia entre el canal vidiano y el palatovaginal de 3,78 mm para(73).…”
unclassified